A Study on Aspects Regarding Assurance Of Guest#x2019;s Safety by Hotel Crowne Plaza, Greater Noida, Post Covid-19 (Global Journal of Management and Business Research, 2022)
People are afraid to come out of their houses due to Covid-19. Physical socializing and interaction with other people has become a threat to life and people are moving towards the virtual ways of interacting with people. This has become a bane for hospitality industry. But still restaurants and hotels are taking necessary precautionary measures for the safety of the guests.
Keywords: safety assurance; covid-19; crowne plaza hotel; precaution